2020
DOI: 10.1177/1534735420952887
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week Multi-Modal Exercise Program: Feasibility of Combined Exercise and Simplified 8-Style Tai Chi Following Lung Cancer Surgery

Abstract: Objective: To assess the feasibility, safety, and preliminary effect of a 12-week multi-modal rehabilitation program targeted at improving health-related quality of life and physical activity levels of patients with lung cancer following treatment. Methods: Patients with stage I to IIIA non-small cell lung cancer were included 6 to 12 weeks following completion of treatment. The intervention comprised of aerobic exercise (brisk walking), resistance training and 8-style Tai Chi. The 12-week program included 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
7
2
Order By: Relevance
“…Thus, we suggest a future study that considers the effects of medication to determine whether exercise can improve such symptoms. The dropout rate in this study was 28.85%, which is not high compared to other studies of patients with lung cancer (16,23,40). This could be attributed to the fact that the patients in the present study were older adults.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Thus, we suggest a future study that considers the effects of medication to determine whether exercise can improve such symptoms. The dropout rate in this study was 28.85%, which is not high compared to other studies of patients with lung cancer (16,23,40). This could be attributed to the fact that the patients in the present study were older adults.…”
Section: Discussioncontrasting
confidence: 74%
“…The dropout rate in this study was 28.85%, which is not high compared to other studies of patients with lung cancer ( 16 , 23 , 40 ). This could be attributed to the fact that the patients in the present study were older adults.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Of the 33 studies included, 16 were pre-post interventions, 13 were randomized controlled trials (RCTs), 3 were pooled analyses of multiple RCTs, and 1 was a quasi-experimental study. The majority of studies were conducted in the US [ 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] or Denmark [ 19 , 34 , 35 , 36 , 37 , 38 ], with the remaining studies conducted in Canada [ 39 , 40 , 41 , 42 , 43 ], China [ 44 , 45 , 46 ], South Korea [ 47 , 48 ], Turkey [ 49 ], Germany [ 50 ], France [ 51 ], the Netherlands [ 52 ], Australia [ 53 ], and Spain [ 54 ]. Most studies (58%) were conducted in 2016 or later; all studies were conducted between 2001 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Tai chi and qi gong have been shown to be good substitutes for routine exercises during rehabilitation therapy [38]. Lu et al [39] found that the combination of tai chi with traditional PR for lung cancer survivors was safe. It is therefore necessary to explore more effective rehabilitation treatments.…”
Section: Discussionmentioning
confidence: 99%